Կրոնական hարաբերությունները Վանի թագավորությունում ըստ Գրիգոր Ղափանցյանի - Սոնա Գրիգորյան (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Ученый-востоковед Григор Капанцян (1887–1957) внес существенный вклад как в армянское урартоведение, так и во всемирное изучение клинописных цивилизаций. Велико его наследие в изучении религиозных отношений в пантеоне Ванского царства. Он первый изучил структуру пантеона классифицируя биайниские божества на шесть групп: три женских и три мужских. Он первым выделил верховных богов пантеона (Халди, Тейшеба и Шивини) и предположил, что эти божества в начальный период были богами разных племен этого региона.The contribution of the famous Armenian scholar and Orientalist Grigor Ghapantsyan (1887–1957) to the Armenian Urartology, as well as to the investigation of the international cuneiform civilizations is great. He was the fi rst to analyze the structure of the pantheon, classifying the deities of Biainili into six groups, three feminine and three masculine deities. He was the fi rst scholar in the fi eld of Urartology who emphasized the existence of that triad, Haldi, Teisheba and Shivin, which makes up the most important part of the Urartian pantheon. In his viewpoint these deities were at fi rst gods of diff erent tribes living in the territory in question.
Keywords: Christianity